L’évolution des paysages de référence, un angle mort dans la gouvernance des paysages ? - Clémence Moreau; Cécile Barnaud; Raphaël Mathevet (Développement Durable et Territoires)
Baseline landscapes play a part in the landscape governance. On the Mont Lozere, France, the institutions aim to preserve open landscapes, which are considered as baseline landscapes. In this paper, we analyse how the open landscape dynamics due to the evolution of farming practices impact the stakeholder interplay and weaken the local governance. Our results show that the evolution of baseline landscapes is a blind spot in the landscape governance. Baseline landscapes are used in the development project as a unifying element, considered as consensual and static. This masks the diversity of representations about baseline landscapes and their dynamics. This case study advocates for considering baseline landscapes as a subject of debate.